A study of tour operators' motivation and views on responsible rural tourism development in Sabah, Malaysia - Tay Kai Xin; Chan, Jennifer Kim Lian (Tourism Educators Association of Malaysia, 2013)
All aspects of sustainability have been widely discussed by researchers and tourism stakeholders for about three decades. The paper presents exploratory research that explores and identifies motivations of tour operators in responding to responsible rural tourism development as well as the challenges and barriers faced by tour operators. This paper also proposes a theoretical framework which is built upon the motivation factors using the push and pull theory to present the initiatives of tour operators in the practice of responsible tourism development in rural destinations.